Response of the porcine MYH4-promoter and MYH4-expressing myotubes to known anabolic and catabolic agents in vitro - Madelaine C. Brearley; David M. Loczenski-Brown; Paul T. Loughna; Tim Parr; John M. Brameld (Biochemistry and Biophysics Reports, 2021)
Myosin heavy chain-IIB (MyHC-IIB; encoded by MYH4 or Myh4) expression is often associated with muscle hypertrophic growth. Unlike other large mammals, domestic pig breeds express MyHC-IIB at both the mRNA and protein level. Aim: To utilise a fluorescence-based promoter-reporter system to test the influence of anabolic and catabolic agents on increasing porcine MYH4-promoter activity and determine whether cell hypertrophy was subsequently induced. Methods: C2C12 myoblasts were co-transfected with porcine MYH4-promoter-driven ZsGreen and CMV-driven DsRed expression plasmids. At the onset of differentiation, treatments (dibutyryl cyclic-AMP (dbcAMP), Des(1–3) Insulin-Like Growth Factor-1 (IGF-I), triiodo-l-thyronine (T3) and dexamethasone (Dex)) or appropriate vehicle controls were added and cells maintained for up to four days. At day 4 of differentiation, measurements were collected for total fluorescence and average myotube diameter, as indicators of MYH4-promoter activity and cell hypertrophy respectively. Results: Porcine MYH4-promoter activity increased during C2C12 myogenic differentiation, with a marked increase between days 3 and 4. MYH4-promoter activity was further increased following four days of dbcAMP treatment and average myotube diameter was significantly increased by dbcAMP. Porcine MYH4-promoter activity also tended to be increased by T3 treatment, but there were no effects of Des(1–3) IGF-I or Dex treatment, whereas average myotube diameter was increased by Des(1–3) IGF-I, but not T3 or Dex. Conclusion: Porcine MYH4-promoter activity responded to dbcAMP, Des(1–3) IGF-I and T3 treatment in vitro as observed previously in reported in vivo studies. However, we report that increased MYH4-promoter activity was not always associated with muscle cell hypertrophy. The fluorescence-based reporter system offers a useful tool to study muscle cell hypertrophic growth.